Safety and Feasibility of a Minimally Fluoroscopic Approach for Ventricular Tachycardia Ablation in Patients With Structural Heart Disease: Influence of the Ventricular Tachycardia Substrate. (February 2016) - Cano, Óscar; Andrés, Ana; Osca, Joaquín; Alonso, Pau; Sancho-Tello, María-José; Olagüe, José; Martínez-Dolz, Luis
Abstract : Background—: We sought to evaluate the safety and feasibility of a minimally fluoroscopic approach using the CARTOUNIVU module during scar-related ventricular tachycardia (VT) ablation. Methods and Results—: Consecutive patients with structural heart disease undergoing VT ablation using the CARTOUNIVU module were prospectively included and classified depending on their VT substrate: (1) ischemic VT (IVT) and (2) nonischemic VT and depending on the presence of an epicardial access. Radiation exposure parameters and major and minor procedure-related complications were registered. A near-zero fluoroscopy exposure was defined as those procedures with an effective dose ⩽1 mSv. A total of 44 VT ablation procedures were performed in 41 patients (22 IVT and 19 nonischemic VT). The use of the CARTOUNIVU module resulted in low levels of radiation exposure: median total fluoroscopy time and effective dose of 6.08 (1.51–12.36) minutes and 2.15 (0.58–8.22) mSv, respectively. Patients with IVT had lower radiation exposure than patients with nonischemic VT (total fluoroscopy time, 2.53 [1.22–11.22] versus 8.51 [5.55–17.34] minutes; P =0.016). Epicardial access was associated with significantly higher levels of radiation exposure. Complications occurred in 4.9% patients, none of them being related to the use of the image integration tool. A near-zero fluoroscopy ablation could be performed in 14 of 44 procedures (32%), 43% of IVT procedures, and 50% of procedures with endocardial access only. Conclusions—: The use of the CARTOUNIVU module during scar-related VT ablation resulted in low levels of radiation exposure. A near-zero fluoroscopy approach can be achieved in up to half of the procedures, especially in IVT patients with endocardial ablation. Abstract : Supplemental Digital Content is available in the text.